2004
DOI: 10.1007/s00417-004-1014-8
|View full text |Cite
|
Sign up to set email alerts
|

Visual improvement during psychophysical training in an adult amblyopic eye following visual loss in the contralateral eye

Abstract: To our knowledge, this is the first report of the new approach of perceptual learning in an adult amblyope after loss of vision in the contralateral eye. Our results represent further evidence that the visual system of adult amblyopes preserves a certain degree of neural plasticity, whether spontaneous or enhanced by training. Furthermore, that plasticity in adults is limited, and early diagnosis and treatment of amblyopia must remain the primary goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
(15 reference statements)
0
22
0
4
Order By: Relevance
“…A number of clinical studies suggest that some recovery from amblyopia is possible well past the classically defined critical period in humans, which generally is considered to last up to ϳ9 years of age (Birnbaum et al, 1977;Simmers and Gray, 1999;Fronius et al, 2004). These studies indicate that long periods of depriving the dominant eye in amblyopes are needed for recovery of vision in the weak eye.…”
Section: Discussionmentioning
confidence: 99%
“…A number of clinical studies suggest that some recovery from amblyopia is possible well past the classically defined critical period in humans, which generally is considered to last up to ϳ9 years of age (Birnbaum et al, 1977;Simmers and Gray, 1999;Fronius et al, 2004). These studies indicate that long periods of depriving the dominant eye in amblyopes are needed for recovery of vision in the weak eye.…”
Section: Discussionmentioning
confidence: 99%
“…The neurosciences had suggested earlier a limitation of the sensitive period up to about 6 years ( [3], extrapolated from animal work, e.g. [4]); more recently, the period of susceptibility to change after enforced use of the amblyopic eye has been extended into adulthood [5][6][7][8]. Accordingly, the recommendations for age limits vary, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the visual acuity of the amblyopic eye can display partial spontaneous recovery following loss of vision in the fellow eye [105][106][107][108][109], but the occurrence of this fortunate response is unpredictable and which factors promote improvement under similar circumstances remains totally unknown. We recently addressed the possibility to rescue visual acuity in long-term deprived adult rats exposed to EE immediately after silencing of retino-thalamic projections of the fellow (non amblyopic) eye due to optic nerve dissection [110].…”
Section: Amblyopia Recovery In Enriched Animalsmentioning
confidence: 99%